2013
DOI: 10.1103/physrevlett.111.166101
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Induced Room-Temperature Ferromagnetism in Hydrogenated Epitaxial Graphene

Abstract: Due to the predominantly surface character of graphene, it is highly suitable for functionalization with external atoms and/or molecules leading to a plethora of new and interesting phenomena. Here we show ferromagnetic properties of hydrogenfunctionalized epitaxial graphene on SiC. Ferromagnetism in such a material is not directly evident as it is inherently composed of only non-magnetic constituents. Our results nevertheless show strong ferromagnetism, which cannot be explained by simple magnetic impurities.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 37 publications
(44 reference statements)
6
106
0
Order By: Relevance
“…Vacancy mediated magnetism occurs in CuO [17] and ZnO [18,19]; oxygen vacancy induced magnetism in zinc peroxide [20] and CeO 2 [21]; and surface vacancy induced magnetism in NiO [22]. Thus, these studies reveal that defects in the form of vacancies are the source of this behavior [11][12][13][14][15][16][17][18][19][20][21][22], however, sustainability of this magnetism up to long-range order requires exigency of the mechanism of interaction among these sources. It was observed that this kind of magnetism is governed by the double exchange mechanism through p-p interactions in Mg-doped SnO 2 [23], as well as B-, C-, and N-doped BeO systems [24].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Vacancy mediated magnetism occurs in CuO [17] and ZnO [18,19]; oxygen vacancy induced magnetism in zinc peroxide [20] and CeO 2 [21]; and surface vacancy induced magnetism in NiO [22]. Thus, these studies reveal that defects in the form of vacancies are the source of this behavior [11][12][13][14][15][16][17][18][19][20][21][22], however, sustainability of this magnetism up to long-range order requires exigency of the mechanism of interaction among these sources. It was observed that this kind of magnetism is governed by the double exchange mechanism through p-p interactions in Mg-doped SnO 2 [23], as well as B-, C-, and N-doped BeO systems [24].…”
Section: Introductionmentioning
confidence: 95%
“…To date, this magnetism is observed in a variety of materials with different sources of origin and is classified accordingly [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…from localized electron states at grain boundaries which form arrays of point defects [4]. In single layer graphene grown on SiC ferromagnetic behavior at room temperature could be detected after hydrogenization [5]. For technical applications having graphene grown on magnetic, metallic substrates seems to be a fruitful approach [6,7].…”
Section: Introductionmentioning
confidence: 99%